Smart Toolkit for Evaluating Information Projects, Products and Services: Second Edition: Part III Evaluation Tools - Technical Centre for Agricultural and Rural Cooperation; Inter-American Institute for Cooperation on Agriculture; Royal Tropical Institute (Technical Centre for Agricultural and Rural Cooperation, 2009)
In Part 3 we look at the evaluation tools.The tools featured here are those that we consider to be well suited to evaluating information projects, products and services.With the increasing demand for information practitioners to evaluate their projects themselves, and not rely on external evaluations, the tools chosen are also seen as suitable for self-evaluation and for fostering learning and stakeholder participation...